Diabetes, Diabetic Retinopathy, and Intravitreal Injection as a Risk Factor of Posterior Capsular Rupture in Phacoemulsification Cataract Surgery :A Systematic Review and Meta Analysis: Oral Presentation - Observational Study - Ophthalmologist - NI LUH PUTU NURINDAH SUKMAWATI; I Gusti Putu Eka Suryawan Widnyana (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : The risk of PCR in patients with diabetes and its sequential complication including diabetic retinopathy and Intravitreal Injection (IVI) was still under debate. This study was aimed to summarize the risk of diabetes, diabetic retinopathy, and intravitreal injection towards PCR events during phacoemulsification cataract surgery. Methods : A systematic literature search was performed up to March 2023 from the last 10 years publications using Medline and Cochrane library databases. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) of diabetes, diabetic retinopathy, and IVI with PCR events were calculated using random-effects models. The quality of included studies was appraised using the Newcastle-Ottawa Scale. Results : Six studies about diabetes, six studies about diabetic retinopathy and seven studies about IVI were included in this meta-analysis. The pooled odds ratios of PCR in eyes with diabetes was 1.22 (95% CI: 1.16-1.28) I2 =0.0%, with the diabetic retinopathy patients was 1.23 (95% CI: 1.13-1.33) I2 =64.3%, and with prior IVI was 1.05 (95% CI: 1.03-1.08) I2 =51%. Conclusion : This meta-analysis emphasize that diabetes, diabetic retinopathy, and previous IVI significantly increase the risk of PCR on future phacoemulsification surgery. Further studies are needed to elucidate the underlying mechanism.